Evaluation of MCV/RDW Ratio and Correlations with Ferritin in Telogen Effluvium Patients: Evaluation of MCV/RDW Ratio in Telogen Effluvium - İbiş, Saadet and Aksoy Saraç, Gülhan and Akdağ, Turan (Dermatology Practical & Conceptual, 2022)
Objective: Telogen effluvium is one of the chronic diseases that affect the quality of life (QoL) in women. The study aimed to evaluate the RDW/MCV ratio and its correlation with ferritin in Telogen Effluvium patients and to reveal their potential role in the etiopathogenesis of Telogen effluvium. Material and Methods: We retrospectively evaluated the medical data of 250 patients who were admitted to the dermatology outpatient clinic between September 2020 and December 2020 with a diagnosis of Telogen effluvium. The control group was created retrospectively from the medical records of 250 healthy individuals. HB, HCT, MPV, MCV, RDW, ferritin, and MCV/RDW ratio of both groups were compared and evaluated statistically. Results: All of the Telogen effluvium patients were women in terms of gender. The mean age of the patient group was 33,11±9,66 years and the mean age of the control group was 34,98±12,37 years. The ratio of MCV/RDW, MPV, MCV, and ferritin is lower in the group with Telogen effluvium compared to the control group and a statistically significant difference was found(p<0.05). However, the correlation between MCV/RDW ratio and ferritin was evaluated in Telogen effluvium patients, and no significant differences were found (p>0.05). Conclusion: Iron deficiency anemia is thought of as a factor in female patients with telogen effluvium. Although the data shows the correction of iron deficiency is insufficient telogen effluvium, we proposed that laboratory tests should be routinely used in the diagnosis and treatment phase of patients who apply with the complaint of hair loss.